Kolaborasi Antara Pemerintah, Pengusaha, Dan Serikat Pekerja Dalam Mewujudkan Hubungan Industrial Yang Harmonis Di Kepulauan Riau - Tini Haryani; Muhammad Ikhsan Syafiq; Oktavia Christina; Mellyana Candra (CV. ITTC INDONESIA, 2023)
Developments in labor law can have a significant impact on realizing harmonious industrial relations. The relationship between the development of labor law and efforts to create harmonious industrial relations from the Protection of Workers' Rights, the development of labor law which aims to protect workers' rights, such as the right to fair wages, reasonable working hours, leave, and the right to organize, can create fairness and certainty in the workplace, reducing the potential for conflict. By paying attention to the continuous development of labor law, the government and employers can create a more stable, fair and harmonious work environment. Compliance with applicable laws can be a strong basis for building positive and sustainable industrial relations. The government has an interest in establishing wage policies, on the one hand, to ensure a decent standard of living for workers/laborers of their families, increase productivity and increase people's purchasing power, on the other hand, wage policies must be able to stimulate investment to encourage economic growth and expand employment opportunities. , and able to withstand the rate of inflation. In research regarding industrial relations collaboration in the Riau Islands (Kepri), qualitative research methods can be used. This research can be carried out by referring to regulations and policies related to industrial relations in Indonesia, such as Law Number 2 of 2004 concerning Settlement of Industrial Relations Disputes in order to realize harmonious industrial relations. The conclusion from collaboration between government, employers and trade unions with the development of labor law is that the involvement of all these parties plays an important role in creating harmonious and sustainable industrial relations.